Assessment of hybrid RANS-LES formulations for flow simulation around the Ahmed body. (15th November 2018) - Guilmineau, E.; Deng, G.B.; Leroyer, A.; Queutey, P.; Visonneau, M.; Wackers, J.
Highlights: Investigations of RANS and hybrid RANS-LES models for the Ahmed body. Accurate prediction of the flow for the slant angle 35° by all turbulence models. Failure of RANS models to predict the flow for the slant angle 25°. Better prediction of the flow for the slant angle 25° with the hybrid RANS-LES models. IDDES model: only model to predict the bubble recirculation on the slant. Abstract: This paper presents an investigation of RANS and DES models for the Ahmed body with 25° and 35° slant angles. The Reynolds number, based on the height of the model and the upstream velocity, is 7.68× 10 5 . Two RANS (Reynolds Averaged Navier–Stokes) models are used: the k − ω SST of Menter and the EARSM (Explicit Algebraic Stress Model), based on the k − ω model. Two hybrid RANS-LES (Large Eddy Simulation) models are used: a DES (Detached Eddy Simulation) and an IDDES (Improved Delay Detached Eddy Simulation). These hybrid models are also based on the k − ω model. The flow for the slant angle 35° is well predicted by all turbulence models with a slight advantage for the IDDES model. For the flow with the slant angle 25°, only the IDDES hybrid RANS-LES model predicts the recirculation bubble on the slant. It is concluded that the IDDES model is the only turbulence model that gives good agreements with the experimental data.